Nerve growth factor and artemin are paracrine mediators of pancreatic neuropathy in pancreatic adenocarcinoma - Ceyhan, Güralp Onur; Schäfer, Karl Herbert; Kerscher, Annika; Rauch, Ulrich; Demir, Ihsan Ekin; Kadihasanoglu, Mustafa; Böhm, Carolin; Müller, Michael W.; Büchler, Markus W.; Giese, Nathalia; Erkan, Murat Mert; Friess, Helmut (Annals of surgery, 2010)
OBJECTIVE: To further characterize the neurotrophic attributes of pancreatic cancer (PCa). - SUMMARY BACKGROUND DATA: PCa is characterized by neuropathic alterations which are resulting in pancreatic pain. To further characterize pancreatic neuropathy, we aimed: to analyze whether neuropathic alterations in PCa are only limited to the tumor-core or whether they are similarly encountered in neural structures in the noncancerous pancreas, to demonstrate whether PCa features neurotrophic attributes and finally to identify responsible neurotrophic molecules. - METHODS: Nerve density and area were quantified in normal pancreas (NP, n=45), histologically "normal" pancreas next to pancreatic cancer (NNPCa, n=61) and PCa (n=97). Growth-associated protein-43, nerve growth factor (NGF), and Artemin expressions were assessed by Immunohistochemistry, Western-Blot, and quantitative real time polymerase chain reaction-analyses. Isolated myenteric plexus of newborn rats were exposed to NP, NNPCa, and PCa tissue extracts and supernatants of Panc1 and T3M4 cancer cells with or without Artemin and NGF depletion, followed by neurite density analysis. - RESULTS: Dense neural networks and enlarged nerves were not only detected in PCa but were also present in NNPCa. Growth-associated protein-43, NGF, and Artemin expressions were absent/weak in NP, but increased in both NNPCa and PCa and were closely associated with intrapancreatic neuropathy. PCa and NNPCa tissue extracts and Panc1/T3M4 supernatants noticeably increased neurite density in myenteric plexus-cultures, which were attenuated by depletion of NGF and Artemin. - CONCLUSIONS: The neurotrophic effects of PCa extend into the peritumoral "normal" pancreatic areas without neuro-cancer interactions. The neurotrophic characteristics of PCa can be mimicked by in vitro analyses and reveal NGF and Artemin as potential key players in the generation of pancreatic neuropathy in PCa.